2007
DOI: 10.1021/jm070285r
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonated Carbocyclic 2‘-Oxa-3‘-azanucleosides as New Antiretroviral Agents

Abstract: Phosphonated carbocyclic 2′-oxa-3′-azanucleosides have been synthesized and tested for their antiretroviral activity. The obtained results have shown that some of the compounds were as powerful as azydothymidine in inhibiting the reverse transcriptase activity of the human retrovirus T-cell leukemia/lymphotropic virus type 1 and in protecting human peripheral blood mononuclear cells against human retrovirus T-cell leukemia/ lymphotropic virus type 1 transmission in vitro. These data indicate that phosphonated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 19 publications
(26 reference statements)
2
25
0
Order By: Relevance
“…In addition, we must note that, using our assays, we found a high discrepancy in the anti-HIV RQIC 50 (inhibition of virus expression) value in comparison with the anti-HIV RTIC 50 (inhibition of RT enzymatic activity) value of the compounds. Interestingly, however, the magnitude of discrepancy we found for HIV-1 in this study is very similar to that we found for HTLV-1 in this and previous 17,31,32 studies with different compounds, using similar assays. Considering their low in vitro toxicity these natural compounds deserve further studies to compare their activity to that of antiretroviral drugs currently available.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we must note that, using our assays, we found a high discrepancy in the anti-HIV RQIC 50 (inhibition of virus expression) value in comparison with the anti-HIV RTIC 50 (inhibition of RT enzymatic activity) value of the compounds. Interestingly, however, the magnitude of discrepancy we found for HIV-1 in this study is very similar to that we found for HTLV-1 in this and previous 17,31,32 studies with different compounds, using similar assays. Considering their low in vitro toxicity these natural compounds deserve further studies to compare their activity to that of antiretroviral drugs currently available.…”
Section: Discussionsupporting
confidence: 90%
“…Allogeneic stem cell transplantation can result in long-term disease control but few patients can be successfully transplanted. 3 Antiretrovirals with activity against HIV-1, such as zidovudine (39-azido-29,39-dideoxythymidine [AZT]) and tenofovir, and new phosphonated compounds, efficiently block HTLV-1 transmission in vitro, [4][5][6][7] whereas HTLV-1 was resistant to lamivudine. 8 Two preliminary phase 2 studies using the combination of AZT and interferon-a (IFN-a) reported an unexpectedly high response rate, particularly in previously untreated acute ATL patients.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Following intracellular phosphorylation to their 5 0 -triphosphate forms, they are able to serve as chain terminators, thus acting as inhibitors in the viral reverse transcription reaction. 18,19 Several strategies to overcome the initial selective phosphorylation step have been designed; 23 in particular, phosphonate analogues, 20 by miming the nucleoside monophosphates, overcome the instability of nucleotides towards phosphodiesterase and enhance the cellular uptake by bypassing the initial phosphorylation step.…”
Section: Introductionmentioning
confidence: 99%